Squamous Epithelium in Respiratory Tract of Children with Tracheo-oesophageal Fistula - Emery, John L. (1971)
Histological study of the trachea and bronchi from 50 children dying with tracheo-oesophageal fistula showed that in 80% there was extensive squamous metaplasia. This change was chiefly in the posterior muscular wall of the trachea, but frequently extended to the lateral and anterior walls of the trachea, and into the bronchi. It is suggested that the primary localization to the muscular trachea is related to the embryology of the congenital deformity, and that secondary factors such as acute infection and oxygen therapy may extend the lesion. The lesion is probably an important factor in the respiratory complications of children with tracheo-oesophageal fistula.